Asuhan Keperawatan Pasien Post Partum Sectio Caesarea Atas Indikasi Letak Sungsang - Tri Nida Amaliyah; Merida Simanjuntak (AKPER Pasar Rebo, 2019)
Childbirth is the process of delivering a conception results (fetus and placenta that was enough for months or can live outside of the womb through the birth canal or another way. The definition of caesarean section is the delivery of a newborn through a surgical incision in the abdomen and front (anterior) wall of the uterus. As for the indications that an increasing number of Caesarean section are fetal malpresentation, repeat Caesarean section, premature birth, high risk prrgnancy, twin pregnancy, pregnancy with pre-eclampsia and failed induction of labor, etc. One indication of sectio caesarea delivery is fetal malpresentation. Fetal malpresentations are abnormal positions of the vertex of the fetal head (with the occiput as the reference point) relative to the maternal pelvis. Malpresentations are all presentations of the fetus other than vertex. WHO in 2013 estimates that labor with caesarean section is around 10% in developing countries, in developed countries such as the United States 23%. In government Hospitals as much as 11% and at home Private illness as much as 30%. In Jakarta, especially in Pasar Rebo Hospital from the results of data in December-March, labor with an indication of breech location was 25 people (2.9%). Post delivery, the mother enters the postpartum period, namely, the recovery period in the post partum mother. In these conditions that need to be considered or the possibility of complications during the puerperium such as infection and bleeding. To prevent complications, comprehensive treatment is needed, by providing care by doing a number of nurse roles, namely promotive, preventive, curative and rehabilitative roles.